Computational prediction of the electronic structure and optical properties of graphene-like β-CuN3. Issue 47 (16th November 2015) - Zhang, Xu; Zhao, Xudong; Jing, Yu; Wu, Dihua; Zhou, Zhen
Abstract : Graphene-like β-CuN3 was investigated by first-principles computations, and its electronic structure and optical properties were disclosed in detail. Abstract : Recently, a new polymorph of the highly energetic phase β-CuN3 has been synthesized. By hybrid density functional computations, we investigated the structural, electronic and optical properties of β-CuN3 bulk and layers. Due to the quantum confinement effect, the band gap of the monolayer (2.39 eV) is larger than that of the bulk (2.23 eV). The layer number affects the configuration and the band gap. β-CuN3 shows both ionic and covalent characters, and could be stable in the infrared and visible spectrum and would decompose under ultraviolet light. The results imply that bulk β-CuN3 could be used as an energetic material.